The interfacial characteristics of falling film reactors - Clark, Wayne William Philip (2001)
Falling film reactors are a very effective geometry in which to carry out fast exothermic gas-liquid reactions, because they allow easy removal of the heat produced. To optimise and improve falling film reactors, soundly based physical models are required. Existing models assume a flat liquid film combined with empirically-determined mass transfer coefficients, but there is growing evidence that this is unsatisfactory, since the interface is dominated by ripples and larger disturbance waves which have a significant effect on the mass and heat transfer rates through and into the film.